Pemberian Makanan Pendamping Air Susu Ibu Terlalu Dini Sebagai Faktor Risiko Terjadinya Kekurangan Gizi pada Balita - Febriana, Citra Nurwidya; Handayani, Tinuk Esti; Suparji, Suparji; Suharto, Agung (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2024)
Most of the causes of under-five deaths are related to malnutrition due to improper feeding practices during infancy, for example giving complementary foods to breast milk that are too early or too late. This study aims to analyze the relationship between the provision of complementary foods for breast milk and the nutritional status of toddlers aged 6-36 months. This study applied a cross-sectional design, involving 88 toddlers aged 6-36 months, who were selected by simple random sampling technique. Data was collected by filling out questionnaires, weighing and measuring height. To analyze the relationship between the two variables, the Kendall's Tau correlation test was used. The results showed that the majority of children under five who were given complementary food to breast milk at the age of <6 months experienced nutritional problems. Meanwhile, the majority of toddlers who were given complementary food for breast milk ≥ 6 months had normal nutritional status. The Kendall's Tau test results showed p-value of 0.000. It could be concluded that there is a relationship between the age at first giving complementary foods for breast milk and the nutritional status of toddlers.Keywords: complementary food for breast milk; toddler; nutritional status ABSTRAK Sebagian besar penyebab kematian balita berkaitan dengan kekurangan gizi akibat praktik pemberian makan yang tidak benar pada masa bayi, misalnya pemberian makanan pendamping air susu ibu yang terlalu dini atau terlambat. Penelitian ini bertujuan untuk menganalisis hubungan antara pemberian makanan pendamping air susu ibu dengan status gizi balita umur 6-36 bulan. Penelitian ini menerapkan rancangan cross-sectional, yang melibatkan 88 balita berumur 6-36 bulan, yang dipilih dengan teknik simple random sampling. Data dikumpulkan melalui pengisian kuesioner, penimbangan berat badan dan pengukuran tinggi badan. Untuk menganalisis adanya hubungan antara kedua variabel digunakan uji korelasi Kendall’s Tau. Hasil penelitian menunjukkan bahwa mayoritas balita yang diberi makanan pendamping air susu ibu pada umur <6 bulan mengalami masalah gizi. Sedangkan mayoritas balita yang diberi makanan pendamping air susu ibu ≥6 bulan memiliki status gizi normal. Hasil uji Kendall’s Tau menunjukkan nilai p = 0,000. Dapat disimpulkan bahwa ada hubungan antara umur pertama pemberian makanan pendamping air susu ibu dengan status gizi balita. Kata kunci: makanan pendamping air susu ibu; balita; status gizi